The Effect of Applying the Mentimeter Media Assisted Problem Based Learning Model on Mathematics Learning Outcomes in Data Presentation Materials - Harahap, Layli Putri Arfianti; Mulyawati, Yuli; Sukmanasa, Elly (International Research-Based Education Journal, 2023)
This research aims to determine the effect of the problem based learning model assisted by note taking on mathematics learning outcomes in data presentation material. The type of research used was quasi-experimental with a nonequivalent control group design. This research was conducted at SDN 1 Lawanggintung, Bogor City, Classes VA and VB as the experimental class and control class. The data from this research were analyzed using Microsoft Excel 2021. Data collection to obtain student learning outcomes tests was obtained using pretest and posttest. The data analysis technique in this research uses the t-test. Based on the results of data analysis from hypothesis testing using the t test, tcount = 4.29258, while ttable at the significant level /2 = 0.025 is 2.00324, then we get tcount > t table, namely 4.29258 > 2.00324 so that Ha is accepted or H 0 is rejected. Thus, there is an influence of the problem based learning model on the learning outcomes of fifth grade mathematics students at SDN Lawanggintung 1.